A Novel Approach for Bladder Cancer Treatment: Nanoparticles as a Drug Delivery System - Zhao X; Qi X; Liu D; Che X; Wu G (International Journal of Nanomedicine)
Xinming Zhao,* Xiaochen Qi,* Dequan Liu,* Xiangyu Che, Guangzhen Wu Department of Urology, The First Affiliated Hospital of Dalian Medical University, Dalian, 116011, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiangyu Che; Guangzhen Wu, Email chexiangyu@firsthosp-dmu.com; wuguang0613@hotmail.comAbstract: Bladder cancer represents one of the most prevalent malignant neoplasms of the urinary tract. In the Asian context, it represents the eighth most common cancer in males. In 2022, there were approximately 613,791 individuals diagnosed with bladder cancer worldwide. Despite the availability of efficacious treatments for the two principal forms of bladder cancer, namely non-invasive and invasive bladder cancer, the high incidence of recurrence following treatment and the suboptimal outcomes observed in patients with high-grade and advanced disease represent significant concerns in the management of bladder cancer at this juncture. Nanoparticles have gained attention for their excellent properties, including stable physical properties, a porous structure that can be loaded with a variety of substances, and so on. The in-depth research on nanoparticles has led to their emergence as a new class of nanoparticles for combination therapy, due to their advantageous properties. These include the extension of the drug release window, the enhancement of drug bioavailability, the improvement of drug targeting ability, the reduction of local and systemic toxicity, and the simultaneous delivery of multiple drugs for combination therapy. As a result, nanoparticles have become a novel agent of the drug delivery system. The advent of nanoparticles has provided a new impetus for the development of non-surgical treatments for bladder cancer, including chemotherapy, immunotherapy, gene therapy and phototherapy. The unique properties of nanoparticles have facilitated the combination of diverse non-surgical therapeutic modalities, enhancing their overall efficacy. This review examines the recent advancements in the use of nanoparticles in non-surgical bladder cancer treatments, encompassing aspects such as delivery, therapeutic efficacy, and the associated toxicity of nanoparticles, as well as the challenges encountered in clinical applications.Keywords: bladder cancer, nanoparticle, drug delivery, chemotherapy, phototherapy, toxicity